Sistem Informasi Booking Homestay Pariwisata Di Kabupaten Sukabumi Berbasis Web - Zainil Abidin; Muhammad Naufal (Cakrawala Repositori IMWI, 2020)
One factor that can provide comfort facilities is the existence of fast information services in carrying out the process of lodging / homestay bookings for customers. In the lodging booking system in the tourist objects in Sukabumi regency there are still obstacles, namely using the manual method, by making a direct order or by telephone. This has the effect of delaying the process of homestay ordering then uncertainty of availability or not. Therefore this research is carried out aims to be able to provide information needed by customers. For homestay owners can increase the effectiveness of ordering work can be faster, accurate and timely because the data processing is done by the system, and the data is stored in the database so that it is safer, tidy and maintained. In this study the author uses structural design methods using SDLC, and website creation using the PHP programming language. The results of this study are that it can facilitate customers to process homestay bookings online. This research was only carried out in the district of Sukabumi which aims to make it easier for customers to place an order without having to come to the homestay while on vacation to the tourist attractions to be visited.